A TRANSNATIONAL EXCHANGE MECHANISM AMONG MOLDOVAN MIGRANTS IN THE PARISIAN REGION: EXPLORING THE “POST OFFICE OF MOLDOVA” - Rosca, Dorina (Economy and Sociology, 2023)
This article delves into the phenomenon of material goods circulation in the context of international migration, specifically looking at the exchange of parcels between Moldovan immigrants in the Paris region, France, and their kin, friends, and acquaintances in Moldova. The analysis uses field data collected during an ethnographic study conducted in 2017 within the Moldovan immigrant community in Paris. It moves beyond the limitations of push-pull theories that focus solely on one-way material circulation from immigrants to their home country families or only on the economic implications of remittances. Adopting a diverse methodological and epistemological stance, the author’s inductive approach highlights the heuristic value of the field data. This data suggests that the parcel exchange between Moldovan immigrants and their compatriots carries significant social and symbolic meaning for all actors involved in this process. Over time, this exchange has evolved into a social institution, creating an ongoing link between the host country and the country of origin. The author scrutinizes the material and symbolic processes involved in the parcel transfer mechanism, whimsically referred to by the migrants as "Post Office of Moldova", the name of the national postal service in Moldova. The article explores both the commercial and non-commercial dynamics that shape this mechanism’s operations and its integrative impact on the Moldovan immigrant community in the Paris region. The motivations that drive these material flows associated with migration are portrayed in terms of reciprocity, redistribution, and altruism, thereby emphasizing the reciprocal nature of these exchanges.